ICT Tools and Resources-A Study of Higher Education in India - Binu Mol T. V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Information and Communication Technology ICT-enabled education includes infrastructures like computers, the internet, telecommunications infrastructure, digital technologies such as smartphones and tablets, and applications used for information processing. Quality Education can be achieved at anytime from anywhere. ICT environments will allow learners and teachers to improve their skills. Mobile-based Apps and tools also can be utilized. Though capital Expenditure for implementing ICT is high, it improves efficiency. It involves the integration of data and analysis and can be used in research and evaluation. The study reviews various ICT tools and resources in the educational process and shows that they significantly improve the educational process. The review covers various e-journal Consortia, e-content Development, and management. The study goes through various planning periods of UGC and ends with current trends in ICT. AI is one of the fastest-growing areas in ICT.